Ecological Awareness: Matrimony of Agriculture and Art - Singh, Santosh Kumar (Social Inquiry: Journal of Social Science Research, 2020)
This article examines how Mithila folk painting reflects ecological consciousness of the society and the intertwined Maithili life with local flora and fauna that consequently maintains natural environment intact in the region. At the onset of climate issue worldwide, folk painting of Mithila communicates its local as well as international spectators about the preservation of surrounding nature blending it with ritual phenomena, agrarian lifestyle and inculcating geographical values to the new generation through the visual depiction. Once the indigenous art, transformed into leading folk painting, due to commercialization has lifted its spiritual veil to worldly affairs. In this course of shift, ecology based painting proves to be a boon for the art lovers and buyers as it attempts to balance the degrading nature with its preservation technique appropriate to its own native land. A pivotal visualization of the merriment of lifespan and landscape amidst spirituality and perpetuity remains the characteristic feature of this indigenous art work.